2017
DOI: 10.12693/aphyspola.132.833
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Titanium Dioxide Synthesis from Synthetic Rutile Waste using a Moderate Acid Concentration and Temperature

Abstract: The present study is to clarify the present influences of acid concentration and temperature of caustic hydrothermal method on extracting the titanium dioxide (TiO2) from synthetic rutile waste. In this experimental work, the caustic hydrothermal method comprises two processes: a decomposition and the sulphate process. The extracted titanium is characterized by using a electron dispersive X-ray spectroscopy to specify its chemical composition, field emission scanning electron microscope to determine the morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Similar The energy-dispersive X-ray spectrum (Figure S1) of the titanium dioxide shows that the catalyst contains two elements: titanium and oxygen (Ti = 76% and O = 24%). Similar results were reported by Qamar et al, 2023 [49], and Mukifza et al, 2017 [53], who reported on the purity of titanium dioxide nanoparticles using EDX.…”
Section: Catalyst Characterizationsupporting
confidence: 90%
“…Similar The energy-dispersive X-ray spectrum (Figure S1) of the titanium dioxide shows that the catalyst contains two elements: titanium and oxygen (Ti = 76% and O = 24%). Similar results were reported by Qamar et al, 2023 [49], and Mukifza et al, 2017 [53], who reported on the purity of titanium dioxide nanoparticles using EDX.…”
Section: Catalyst Characterizationsupporting
confidence: 90%
“…Most research in natural sciences and technology depends on the design and implementation of the research experiment [1][2][3][4][5]. Given the importance of experimentation in the natural sciences and technology, different teaching methods and mathematics methods have recently been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by the authors have shown some promising results with modified hydrothermal TiO 2 extraction [ 7 , 20 , 21 ], including demonstrating its ability to eradicate respiratory bacteria and fungus through self-disinfection [ 12 , 22 , 23 ]. Previous experiments with nanotitanium dioxide have also resulted in the suppression of its mutagenic capability [ 23 ] and its toxicological properties [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%